Immune checkpoint inhibitors in cancer patients with autoimmune disease: Safety and efficacy - Jiayuan Le; Yuming Sun; Guangtong Deng; Yating Dian; Yanli Xie; Furong Zeng (Human Vaccines & Immunotherapeutics)
The utilization of immune-checkpoint inhibitors (ICIs) in cancer immunotherapy frequently leads to the occurrence of immune-related adverse events (irAEs), making it generally not recommended for patients with preexisting autoimmune diseases. Hence, we conducted a meta-analysis on safety and efficacy of ICIs in cancer patients with preexisting autoimmune diseases to provide further insights. PubMed, EMBASE, and Cochrane Library were systematically searched until December 20, 2024. The main summary measures used were pooled rate and risk ratio (RR) with 95% confidential interval (CI), which were analyzed using R statistic software. A total of 52 articles were included in the study. When cancer patients with preexisting autoimmune diseases received ICIs treatment, the overall incidence was 0.610 (95% CI: 0.531–0.686) for any grade irAEs, 0.295 (95% CI: 0.248–0.343) for flares, 0.325 (95% CI: 0.258–0.396) for de novo irAEs, 0.238 (95% CI: 0.174–0.309) for grade ≥3 irAEs, and 0.143 (95% CI: 0.109–0.180) for discontinuation due to immunotoxicity. Compared with those without autoimmune diseases, cancer patients with autoimmune diseases experienced a higher risk of any-grade irAEs (RR: 1.23, 95% CI: 1.12–1.35) and discontinuation due to immunotoxicity (1.40, 95% CI: 1.11–1.78). However, no statistically significant differences were observed in the incidence of grade ≥3 irAEs, objective response rate (ORR), disease control rate (DCR), overall survival (OS), and progression-free survival (PFS) between the two groups. During ICIs treatment, irAEs are common among cancer patients with autoimmune diseases, but severe irAEs is relatively low. ICIs are effective in this population, but should be strictly monitored when used to avoid immunotoxicity.